GLOBAL VALUE CHAINS: WORLD TRENDS AND THE RUSSIA’S INVOLVEMENT - T. A. Meshkova; E. Ja. Moiseichev (Финансы: теория и практика)
The paper considers the main theoretical approaches to understanding global value chains (GVC) and analyzes their role in the modern global economy. It is emphasized that in view of the growing political and economic importance of the GVC, today this phenomenon is in the focus of many countries and international institutions including the «Group of Twenty» (G20), the Organization for Economic Cooperation and Development (OECD), the World Trade Organization (WTO), the United Nations Conference on Trade and Development (UNCTAD) and the World Bank. To describe the major world trends in the GVC and characteristic aspects of Russia’s involment in the GVC, the paper uses, inter alia, the most recent data obtained through applying the TiVA (Trade in Value-Added) methodology which was developed jointly by the OECD and the WTO.The current state of Russia’s participation in the GVC proves that Russia is mainly involved in the upstream GVC part (i.e. other countries use exported Russian goods as raw materials or components in their production). The current position of Russia in the GVC does not provide long-term benefits for our country nor meet the medium and long-term objectives of social and economic, scientific and technological development.The authors explore the barriers as well as factors facilitating the participation of Russia in the GVC. In conclusion, recommendations are made to improve the effectiveness of Russia’s involvement in the GVC. The suggested measures include both horizontal measures related to the comprehensive modernization of the economy and public administration as well as measures aimed at a more adequate assessment, monitoring and forecasting of participation in the GVC through active international cooperation in this field.